Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Di Toko Giordano Area Denpasar Dan Badung - Ni Putu Eva Hendayani; Ni Luh Sili Antari; I Gusti Agung Bagus Widiantara (Universitas Triatma Mulya, 2025)
Employee performance is a crucial aspect of any company, as it significantly impacts the achievement of goals. This study examines the influence of work discipline and work motivation on employee performance at Giordano Stores in the Denpasar and Badung areas. The population consisted of 57 respondents. This study used this population as a sample. Data analysis techniques used were descriptive analysis, instrument testing, classical assumption testing, multiple linear regression analysis, t-test analysis, determination analysis, and beta analysis. The conclusion is that work discipline and work motivation partially have a positive and significant influence on employee performance, as indicated by the positive regression coefficients. The magnitude of the influence of work discipline and work motivation on employee performance is 81.2%. The independent variables with a dominant influence on employee performance, as seen in the Standardized Coefficients Beta values, are work motivation, at 0.699, and work discipline, at 0.254.